Men in black [videorecording (DVD)] - Sonnenfeld, Barry; Jones, Tommy Lee, 1946-; Smith, Will, 1968-; Fiorentino, Linda; Cunningham, Lowell, 1959- (Columbia TriStar Home Video, 1997)
New York City is being threatened by a villainous bug who has inhabited the body of a farmer. The mission is to locate and exterminate the bug before it destroys the planet.